The effects of systematic unloading on muscle activation and fatigue during resistance exercise - Chaney, G. K. (ISBS Proceedings Archive (Michigan), 2020)
This study examined acute, local muscle fatigue and recovery, temporally, during velocity-based resistance exercise. A dynamic single-leg extension resistance exercise model with systematic unloading based on changes in repetition velocity was used to measure changes in quadriceps muscle activation patterns. EMG indices of acute, local muscle fatigue and recovery were closely associated with changes in movement velocity for each unloading condition. Systematic Unloading (SU) is an effective resistance training protocol in order to minimize acute, local muscle fatigue and facilitate muscle fatigue recovery within a set